(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Clandestine Detention Centers and task forces were two si- des of the same device: Clandestine Detention Centers hid the presence of perpetrators and perpetrators consistently denied the existence of Clandestine Detention Centers. Hu- man Rights organizations fight to reveal the relation bet- ween this both sides of mechanism of disappearance. They used to identify repressors and its military functions in or- der to make then visible and send to trial. This article asks for the way in which the figure of the repressor is included, presented and represented as part of cultural memory in Ex ESMA. The aim interest is to analyze aesthetic and po- litical mediations that enable (re)presentations of the figure of repressor -instead, names, voices and social valorization- appear in places of memory generally preserved as site for reparation and for memories transmission.